The Problem of Environmental Pollution with Microplastics: Sources, Scale and Possible Solutions - S. A, Mamatkarimova; D. S., Tuychieva; A. K., Khusanov (American Journal of Botany and Bioengineering, 2025)
The article examines the problem of environmental pollution with microplastics, its main sources, scale of distribution and impact on the ecosystem. The factors contributing to the increase in the amount of microplastics in nature are analyzed, including the textile industry, wear of car tires and shortcomings of wastewater treatment facilities. The consequences of pollution for marine organisms, food chains and global ecology are considered. Particular attention is paid to the need for standardization of methods for studying microplastics, as well as possible solutions to the problem, such as the development of biodegradable plastics, improvement of cleaning technologies and improved waste management. The importance of an integrated approach, including scientific developments, government measures and public initiatives, to reduce the level of environmental pollution with plastics is emphasized.